Redescription of the type species of the genus Cypretta (Ostracoda, Crustacea), with notes on the taxonomy of the genus - Ferreira, Vitor Góis; Higuti, Janet; Martens, Koen (Zootaxa, 2023)
With 53 formally described species, the genus Cypretta is one of the most common freshwater ostracod genera in the world. It has a mainly circumtropical distribution. The type species, Cypretta tenuicauda (Vávra, 1895), was described from Zanzibar (Africa) in a superficial way. Therefore, the morphology and identity of this species and of the genus remained problematic until today. Here, we redescribe Cypretta tenuicauda from the original type material and discuss the morphology of the species and the diagnosis of the genus. The species is characterized by the presence of anterior marginal septa in both valves, the sub-triangular carapace shape in lateral view, the right valve overlapping the left valve, the generally wide carapace and the presence of a serrated posteroventral inner list in the right valve. In addition, both α and β setae on the mandibular palp are long and thin, claws Ga and Gp on the caudal ramus are elongated and seta-like, while the caudal ramus itself is equally slender. The caudal ramus attachment is reduced to a simple branch. The present redescription of the type species will assist in creating order in what is now a taxonomically confused genus.